THE INFLUENCE OF FINANCIAL REPORTING COMPLIANCE, GOVERNMENT PERSONNEL COMPETENCY TOWARDS FRAUD PREVENTION IN VILLAGE FUND MANAGEMENT " (CASE STUDY IN KECAMATAN SIMAN KABUPATEN PONOROGO) - Titin Eka Ardiana; La Ode Sugianto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to examine the effect of financial reporting compliance, the competence of government officials on fraud prevention in the management of village funds, both partially and simultaneously. The approach used in this research is quantitative research because the main objective of this study is to prove the relationship, influence, and cause and effect of one variable on another. In this study, there are two kinds of variables used, namely the dependent variable and the independent variable. The dependent variable used for this study is fraud prevention (fraud), while the independent variable used in this study consists of financial reporting compliance and government apparatus competence. The data collection technique in this study is to use primary data, namely a questionnaire (questionnaire). The method of analysis used in this study is to use multiple linear regression analysis using calculations through SPSS version 22. The data collection technique in this study uses a questionnaire distribution technique, namely data collection using a questionnaire technique which is carried out by giving a set of written questions to respondents for answered. The results of data collection were then analyzed using simple regression analysis techniques and multiple regression with the help of SPSS Version 22. The results showed that compliance with financial reporting and the competence of government officials had a significant effect on Fraud Prevention by Apparatus in Villages in Siman District, Ponorogo Regency.